Setting the stage for individualized therapy in hemophilia: What role can pharmacokinetics play?. Issue 4 (July 2018) - Hazendonk, H.C.A.M.; van Moort, I.; Mathôt, R.A.A.; Fijnvandraat, K.; Leebeek, F.W.G.; Collins, P.W.; Cnossen, M.H.; ,
Abstract: Replacement therapy with clotting factor concentrates (CFC) is the mainstay of treatment in hemophilia. Its widespread application has led to a dramatic decrease in morbidity and mortality in patients, with concomitant improvement of quality of life. However, dosing is challenging and costs are high. This review discusses benefits and limitations of pharmacokinetic (PK)-guided dosing of replacement therapy as an alternative for current dosing regimens. Dosing of CFC is now primarily based on body weight and based on its in vivo recovery (IVR). Benefits of PK-guided dosing include individualization of treatment with better targeting, more flexible blood sampling, increased insight into association of coagulation factor levels and bleeding, and potential overall lowering of overall costs. Limitations include a slight burden for the patient, and availability of closely collaborating, experienced clinical pharmacologists.